U-Pb calcite geochronology, EPR, geochemistry, and C-O-Sr isotopes of ancient marbles in the İznik Region (Bursa-Türkiye) - Aysal, Namık; Karslıoğlu, Özge; Erdem, Emre; Guillong, Marcel; Öngen, Sinan; Uysal, İbrahim; Kaygısız, Ersin; Yıldırım, İpek (TÜBİTAK, 2025)
The İznik city (ancient Nicaea), located east of Lake İznik (known as -“Bithynia” in ancient times), has been an important political and cultural centre of Asia Minor since the Hellenistic period. Marbles produced in the quarries in the vicinity (Ömerli and İnikli villages, Deliktaş-Sarıtaş hills) were used both in the construction of the walls and in many ancient works in the city. Approximately eighteen ancient marble quarries producing grey and white marbles were investigated in the region. Petrography, EPR, XRD, C-O-Sr isotope and whole rock geochemistry analyses were performed for characterization of the samples collected from the quarries for the provenance studies. According to the new geochemistry and C-O-Sr isotope data, the limestones forming the marbles were deposited in open sea-ocean environments. U-Pb calcite dating determined that the white marbles were 93.06 ± 8.55 Ma, while the grey marbles were 94.84 ± 1.41 Ma and 88.03 ± 2.13 Ma (Upper Cretaceous: Cenomanian-Coniacian). These ages probably correspond to the crystallization/metamorphism ages of the marbles. The new data set obtained with this study will contribute to the understanding of the geological evolution of the region, and will help researchers to better understand the source region of some white and grey marbles used in ancient buildings.
Keywords: Ancient Marble; Bigio Antico; Nicaea; U-Pb Calcite Dating